Ten simple rules for measuring the impact of workshops. - Shoaib Sufi; Aleksandra Nenadic; Raniere Silva; Beth Duckles; Iveta Simera; Jennifer A de Beyer; Caroline Struthers; Terhi Nurmikko-Fuller; Louisa Bellis; Wadud Miah; Adriana Wilde; Iain Emsley; et al. (PLoS Computational Biology, 2018)
Workshops are used to explore a specific topic, to transfer knowledge, to solve identified problems, or to create something new. In funded research projects and other research endeavours, workshops are the mechanism used to gather the wider project, community, or interested people together around a particular topic. However, natural questions arise: how do we measure the impact of these workshops? Do we know whether they are meeting the goals and objectives we set for them? What indicators should we use? In response to these questions, this paper will outline rules that will improve the measurement of the impact of workshops.